Transformasi Leksikal Penerjemahan Kata-Kata Budaya Jawa ke dalam bahasa Inggris pada Novel Bahasa Indonesia Anak Bajang Menggiring Angin - Pujianti, Kiki; Sajarwa (Humanis, 2025)
Lexical transformation in translation is a process aimed at achieving semantic equivalence from the source language to the target language. This study seeks to identify the types of lexical transformations applied in the translation of Javanese cultural terms and to examine their implications for Javanese cultural identity. The data sources for this study are the novel Anak Bajang Menggiring Angin and its English translation Herding the Wind. A qualitative descriptive method is employed to thoroughly investigate the translation issues. The findings indicate that four types of lexical transformations are used in translating Javanese cultural terms, namely: (1) substitution, (2) addition, (3) omission, and (4) zero transformation. The implications of these transformations for Javanese cultural identity can be categorized into two main tendencies. Most Javanese cultural terms translated into the target language undergo cultural meaning distortion. However, some terms are deliberately retained by the translator as part of an effort to preserve and represent the source culture.